Phrenic nerve stimulation mitigates hippocampal and brainstem inflammation in an ARDS model - Bassi, Thiago G.; Rohrs, Elizabeth C.; Fernandez, Karl C.; Ornowska, Marlena; Nicholas, Michelle; Wittmann, Jessica; Gani, Matt; Evans, Doug; Reynolds, Steven C. (Frontiers in Physiology, 2023)
Rationale: In porcine healthy-lung and moderate acute respiratory distress syndrome (ARDS) models, groups that received phrenic nerve stimulation (PNS) with mechanical ventilation (MV) showed lower hippocampal apoptosis, and microglia and astrocyte percentages than MV alone. Objectives: Explore whether PNS in combination with MV for 12 hours leads to differences in hippocampal and brainstem tissue concentrations of inflammatory and synaptic markers compared to MV-only animals. Methods: Compare tissue concentrations of inflammatory markers (IL-1, IL-1, IL-6, IL-8, IL-10, IFN-, TNF and GM-CSF), pre-synaptic markers (synapsin and synaptophysin) and post-synaptic markers (disc-large-homolog 4, N-methyl-D-aspartate receptors 2A and 2B) in the hippocampus and brainstem in three groups of mechanically ventilated pigs with injured lungs: MV only (MV), MV plus PNS every other breath (MV+PNS50%), and MV plus PNS every breath (MV+PNS100%). MV settings in volume control were tidal volume 8 ml/kg, and positive end-expiratory pressure 5 cmH2O. Moderate ARDS was achieved by infusing oleic acid into the pulmonary artery. Measurements and Main Results: Hippocampal concentrations of GM-CSF, N-methyl-D-aspartate receptor 2B, and synaptophysin were greater in the MV+PNS100% group compared to the MV group, p=0.0199, p=0.0175, and p=0.0479, respectively. The MV+PNS100% group had lower brainstem concentrations of IL-1β, and IL-8 than the MV group, p=0.0194, and p=0.0319, respectively; and greater brainstem concentrations of IFN-g and N-methyl-D-aspartate receptor 2A than the MV group, p=0.0329, and p=0.0125, respectively. Conclusion: In a moderate-ARDS porcine model, MV is associated with hippocampal and brainstem inflammation, and phrenic nerve stimulation on every breath mitigates that inflammation.